On delta-graphs and delta conjecture - Díaz Navarro, Pedro (2018)
In this paper we define two infinite families of graphs called C-δ graphs and -graphs and prove that δ-graphs satisfy delta conjecture. Also we see that C-δ graphs family contains the complements of δ-graphs. Finally we give a list of C-δ graphs and the relationship with the minimum semidefinite rank of these graphs.